The Effect of Particle Size Reduction from Ibuprofen Tablet to Ibuprofen Pulveres on Its Dissolution Rate, Dissolution Profile, and Drug Stability - Angi Nadya Bestari; T.N. Saifullah Sulaiman; Dita Ayu Purnamasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
A factor that influences the release of active ingredient from its dosage form is total particle surface area of drugs that contact with medium. The smaller size of particle can increase the particle surface area which can influence its dissolution and stability. This study aimed to determine the effect of tablet particle size reduction to its organoleptic properties, dissolution rate, dissolution profile, and stability after storage periods of 1, 2, 3, and 4 weeks. Ibuprofen tablet was changed its form by crushing into pulveres dosage form. The pulveres dissolution was conducted by USP type II dissolution tester (paddle method) with phosphate buffer pH 7,2 as the medium. The results of dissolution testing included the value of Q30, DE45, and dissolution rate constant (k). The similarity of dissolution profiles for each preparation could be known by the calculation of similarity factor (f2). Dissolution results showed that changed in particle sizes from the tablet to pulveres could increase dissolution rate constant from 0,063/minute to 0,347/minute and 0,298/minute (p = 0,029) and the DE45 value from 66,52% to 96,76% and 96,17% (p = 0). Pulveres were stable for 4 weeks of storage which were shown by there were not any changes in organoleptic properties. Furthermore, the value of DE45 (%), dissolution rate constants (k) and levels of active substances were not significantly different (p> 0,05) after 4 weeks of storage. The f2 value of ibuprofen tablet and ibuprofen pulveres was under 50 that meant the dissolution profil among them was not similar.